Laccases produced by Peniophora from marine and terrestrial origin: A comparative study - de Jesus Fontes, Bruno [UNESP]; Kleingesinds, Eduardo Krebs; Giovanella, Patricia [UNESP]; Junior, Adalberto Pessoa; Sette, Lara Durães [UNESP] (Elsevier, 2021)
Although fungal laccases have been widely applied in environmental and industrial processes, little is known about laccases produced by marine fungi. In this study, the laccases from basidiomycetes of marine (Peniophora sp. CBMAI 1063) and terrestrial (Peniophora cinerea CCIBt 2541) origin were compared. Using crossflow filtration and anionic exchange chromatography, these laccases were partially purified and characterized. The marine fungus produced two laccase isoforms, whereas the terrestrial strain produced five. The enzymatic pool of the terrestrial Peniophora showed higher affinity (KM) with the tested substrates. On the other hand, laccases from the marine fungus presented higher thermal resistance. The optimum temperature (55 °C) and pH values (4.0 with ABTS and 5.5 with SYG) were the same for both fungi. No significant difference was observed in the reactive blue dye decolorization rates (from 61.17 to 67.38%) after incubation with the laccases from both Peniophora strains and the pure commercial laccase from Trametes versicolor. The increase in toxicity only observed in the experiments using the laccases from the marine Peniophora strain indicates different decolorization mechanisms. This is the first report on reactive blue textile dye decolorization by laccases from the genus Peniophora, expanding their potential for biotechnological application. In this study, the adaptation of the Peniophora strains to the environments from where they were isolated was evidenced, and differences in their laccase isoforms and enzymatic characteristics were observed. The results highlight the advantage of the marine-derived fungus for laccase production under saline conditions and improve the knowledge on marine enzymes.
Keywords: Anionic exchange chromatography; Basidiomycetes; Bioremediation; Crossflow filtration; Enzyme kinetics; Marine enzymes